The Complexities of Annual Reserved Land Leasing in Indonesia: Insights From A Specific Local Context - Ishaka, Mukhlis; Hidayat, Rahmad (Universitas Sultan Ageng Tirtayasa, 2024)
Taking economic benefits from reserved land became a considerable business for many local governments worldwide, including the Bima Regency Government, through an annual leasing policy. Besides its success story, which can increase regional original income, the policy implementation also leaves complicated problems, often characterized by the tension of the struggle for management rights and negative accusations regarding the auction process, which needs to be more transparent. This article discusses an empirical case about the tension of actor relations in the scramble for limited resources in a local context, where the authors conducted in-depth interviews with several informants who were selected through purposive sampling techniques, including those in charge, directors, and leaders of the Regency Level Committee, as well as individual participants, both those who won and lost in the annual leasing auction. Although the land leasing policy can increase local original income and provide opportunities for landless residents to engage in agricultural activities, the auction practice is often marked by a need for more transparency and conflicts of interest. Such a conflict is especially evident in the uneven auction process, which tends to trigger stakeholder tensions. This policy has yet to be entirely successful in supporting land conservation for long-term agricultural production regarding the threat of land degradation due to excessive exploitation.